Economic communique ([s.n.] [S.l], 1996)
Reviews the global economic outlook, urges continued reform of the United Nations and calls for greater flexibility in labour markets as a necessary component of sound macro-economic policies. Gives high priority to achieving a multilateral agreement on investment under the auspices of the Organization for Economic Cooperation and Development (OECD) by June 1997 and to completing an agreement liberalizing global trade in financial services by December 1997.
DC